Analisis Performa Layanan Digital: Eksplorasi Mendalam atas Sistem Informasi BCA Mobile - Tan Evan Tandiyono; Randy Dwi Tinara; Dava Rizqi Al-Fajri; Alvin Ega Pramana (Journal of Science, Technology, and Innovation, 2025)
This study analyzes the performance of various features in the BCA mobile application (mBank BCA), including transfers, payments, purchases, balance inquiries, QRIS, and cardless withdrawal, as part of a broader effort to enhance digital banking services. The research focuses on examining system responsiveness, the stability of integration between the mobile application, backend servers, and relevant devices, as well as multilayered security mechanisms that protect each stage of transactions. Using a qualitative approach, the study draws on system analysis and user experiences to understand how these features operate under different usage conditions. The findings reveal that the features perform consistently and efficiently, with rapid transaction processing, accurate real-time verification, and minimal errors across various services. The implementation of one-time codes, short validity periods, and encryption protocols significantly strengthens security and minimizes potential risks. Furthermore, seamless communication between the mobile system and server or device infrastructure ensures a smooth user experience without compromising safety. Overall, the study concludes that mBank BCA features represent effective digital innovations that enhance service flexibility and reliability, providing a reference model for the development of similar banking technologies in the future.